Depression among Patients with Diabetes Mellitus: Associated Factors and its Prevalence - Muhammad Saeed Khan, Rizwan Farooq, Saima Afsar, Muhammad Fahim Qasim, Shafqat Huma, Usman Amin Hotiana (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The depression and diabetes both are important community health concerns. Depression is a common comorbid disease in diabetic patients. The goal of this analysis was to assess the depression prevalence in diabetic patients and to recognise the numerous influences related with it. Study Design: A cross-sectional study. Place and Duration: In the Psychiatry and Medicine department of Behavioral Sciences, LGH Lahore, Pakistan and Psychiatry Alfalah diagnostic centre, Azhar Medical Plaza Timergara for the duration of six months from July 2021 to December 2021. Methods: The patients with diabetes mellitus who visited the OPD Internal Medicine Department and Psychiatry department were referred for a psychiatric assessment. 140 total patients were studied for 6-month period. Face-to-face interviews were directed to collect the clinical profile and sociodemographic data of the subjects. To classify and describe depression; Patient Health Questionnaire-9 was applied. The percentage, frequency, multivariate regression and test were applied. Results: The total depression prevalence was 30.2% and institute to be higher significantly in women (p = 0.008), subjects on insulin treatment (p = 0.028), diabetes mellitus >15 years (p = 0.049) and patients with uncontrolled blood glucose levels (p = 0.018) even after treatment. A regression analysis found that the type of treatment, blood glucose level, gender, and type of treatment were independent forecasters of depression in patients with DM. The subjects treated with insulin were 4 times additional probable to develop depression (CI: 2.129 - 8.865, OR = 4.344, p <0.001). Conclusion: About a quarter of diabetic patients had depression. Influences such as long duration of diabetes mellitus, female gender, uncontrolled diabetes and therapy with insulin increase the danger of rising depression in patients with diabetes mellitus. Therefore, routinely assessment of depression in diabetic patients is essential.